Pengembangan Media Pembelajaran Puzzle Berbasis Make A Match Pada Materi Bagian-Bagian MataDan Fungsinya Pembelajaran IPAS Kelas V SDN 1 Gondang - Zanuba Aulian Nisa; Rahmad Setyo Jadmiko (MERDEKA : Jurnal Ilmiah Multidisiplin, 2024)
The research was motivated by the initial findings at the time of observation even though the puzzle has been implemented, there is still a need for further development by utilizing interesting and fun media. This study aims to develop and describe the results of the validation of learning media and the application of Make A Match Based Puzzle media on the Material of Eye Parts and Their Functions of Learning Science Class V SDN 1 Gondang. This study uses a 4D development research model (Define, Design, development, Dissemination). Validity is determined by media validation, material expert validation. The validation of Puzzle media received a percentage result of 92% with the category "very valid". The results of the assessment of the subject matter experts received a percentage score of 84.4% with the category of "very valid". The results of the assessment of the responses of class V students were assessed based on the field trial stage on 19 class V students with a percentage score of 89.74 with the category of "very valid" and suitable for use in the learning process.